Computed Tomography Versus Invasive Coronary Angiography in Patients With Diabetes and Suspected Coronary Artery Disease - Benedek, Theodora; Wieske, Viktoria; Szilveszter, Bálint; Kofoed, Klaus F; Donnelly, Patrick; Rodriguez-Palomares, José; Erglis, Andrejs; Veselka, Josef; Šakalytė, Gintarė; Ađić, Nada Čemerlić; Gutberlet, Matthias; Diez, Ignacio; et al. (Diabetes care, 2023)
OBJECTIVE: To compare cardiac computed tomography (CT) with invasive coronary angiography (ICA) as the initial strategy in patients with diabetes and stable chest pain. RESEARCH DESIGN AND METHODS: This prespecified analysis of the multicenter DISCHARGE trial in 16 European countries was performed in patients with stable chest pain and intermediate pretest probability of coronary artery disease. The primary end point was a major adverse cardiac event (MACE) (cardiovascular death, nonfatal myocardial infarction, or stroke), and the secondary end point was expanded MACE (including transient ischemic attacks and major procedure-related complications). RESULTS: Follow-up at a median of 3.5 years was available in 3,541 patients of whom 557 (CT group n = 263 vs. ICA group n = 294) had diabetes and 2,984 (CT group n = 1,536 vs. ICA group n = 1,448) did not. No statistically significant diabetes interaction was found for MACE (P = 0.45), expanded MACE (P = 0.35), or major procedure-related complications (P = 0.49). In both patients with and without diabetes, the rate of MACE did not differ between CT and ICA groups. In patients with diabetes, the expanded MACE end point occurred less frequently in the CT group than in the ICA group (3.8% [10 of 263] vs. 8.2% [24 of 294], hazard ratio [HR] 0.45 [95% CI 0.22-0.95]), as did the major procedure-related complication rate (0.4% [1 of 263] vs. 2.7% [8 of 294], HR 0.30 [95% CI 0.13 - 0.63]). CONCLUSIONS: In patients with diabetes referred for ICA for the investigation of stable chest pain, a CT-first strategy compared with an ICA-first strategy showed no difference in MACE and may potentially be associated with a lower rate of expanded MACE and major procedure-related complications.
Keywords: bolesti na hrudi; prediktivní hodnota testů; diabetes mellitus; Diabetes Mellitus; koronární angiografie; Chest Pain; Tomography, X-Ray Computed; počítačová rentgenová tomografie; lidé; CT angiografie; Coronary Artery Disease; Computed Tomography Angiography; Humans; Coronary Angiography; Predictive Value of Tests; nemoci koronárních tepen